Diversity and characterization of entomopathogenic fungi from rhizosphere of maize plants as potential biological control agents - NOVRI NELLY; MY SYAHRAWATI; HASMIANDY HAMID; TRIMURTI HABAZAR; DWI NASRI GUSNIA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nelly N, Syahrawati MY, Hamid H, Habazar T, Gusnia DN. 2019. Diversity and characterization of entomopathogenic fungi from rhizosphere of maize plants as potential biological control agents. Biodiversitas 20: 1435-1441. The diversity and characters of entomopathogenic fungi in soil are influenced by cultivation techniques. This study aims at determining the characters and pathogenicity of entomopathogenic fungi in maize plant. Materials were extracted from maize plant rhizosphere at different planting system (monoculture, polyculture, and monoculture of corn on formerly oil palm plantation or replanting) in Nagari Koto Baru, Luhak Nan Duo Subdistrict, West Pasaman District, and West Sumatra Province. Insect bait and series dilution were used to carry out the isolation, while Tenebrio molitor larvae were used for the pathogenicity test. Parameters observed include macroscopic and microscopic characteristics, and pathogenicity of entomopathogenic fungi. The result shows that there are three types of entomopathogenic fungi with various features. After identification, it was known that Aspergillus and Metarizium were obtained from mono, polyculture and by replanting crops, while Beauveria was found from the rhizosphere of corn grown in polyculture with pathogenicity identified as one of the high causes of death to larvae T. molitor with LT50 ranging from 48.03-48.48 hours. Key words: Characterisation, diversity, entomopathogenic fungi, rhizosphere